Penerapan Model Structural Equation Modeling (SEM) Dalam Menganalisis Fungsi Manajemen Sumber Daya Manusia Terhadap Kinerja Karyawan Bank Syariah Indonesia - Friska Sari , Istiani; Anita, Anita (Banque Syar'i: Jurnal llmiah Perbankan Syariah, 2024)
This research was conducted at Bank Syariah Indonesia KCP Tangerang Cimone 1 to determine the impact on employee performance. Employee performance refers to the output of employees in carrying out their work over a specific period based on the responsibilities assigned to them. Education, career development, and work experience are closely related to employee performance, and thus the company must have high-performing employees. To draw conclusions, the researcher distributed questionnaires to 43 respondents, which were then analyzed using SemPLS software version 3.0. The results of this study indicate that the variables of education and work experience have a positive impact on the employee performance of BSI KCP Tangerang Cimone 1. However, the career development variable does not have an impact on the employee performance of BSI KCP Tangerang Cimone 1. This study has the limitation of focusing solely on the employees of BSI KCP Tangerang Cimone 1